Distorted octahedral S-methyl 2-(2-oxoindolin-3-ylidene) hydrazinecarbodithioate (SMISA) tridentate schiff base complex of Co(II): synthesis, characterization and structural studies - Abdul Manan, M. A. F.; Tahir, M. I. M.; Crouse, K. A.; How, Fiona Ni Foong (Malaysian Institute of Chemistry, 2020)
Schiff base ligand S-methyl 2-(2-oxoindolin-3-ylidene)hydrazinecarbodithioate, SMISA (1) obtained by condensation of S-methyldithiocarbazate with isatin has been used to synthesized a cobalt(II) complex, namely Co(SMISA)2DMSO (2). The metal complex (2) was formed by reacting Schiff base (1) with cobalt(II) acetate tetrahydrate. These compounds have been characterized by a variety of physico-chemical techniques including FT-IR spectroscopy, elemental analysis, magnetic susceptibility, UV-Vis spectroscopy, molar conductivity, ICP-AES analysis, and single-crystal X-ray diffraction. The crystal structure analysis of the bis-ligand cobalt(II) complex, Co(SMISA)2DMSO (2) revealed that the central Co(II) ion was six coordinate with a distorted octahedral geometry. The X-ray result also showed that the ligand in the thione form was transformed into the thiol form upon coordination to Co(II) ion. The Schiff base acted as a monoanionic tridentate NOS (nitrogen-oxygen-sulphur) chelating agent, coordinating the Co(II) metal center via azomethine nitrogen atoms (N7 and N23), thiolate sulphur atoms (S2 and S18), and carbonylic oxygen atoms of the isatin moiety (O13 and O26).